Corticosteroid-resistant bulbar neurosarcoidosis responsive to intravenous immunoglobulin. Issue 4 (2nd May 2015) - Shenoy, Niraj; Tesfaye, Melaku; Brown, Joshua; Simmons, Nichelle; Weiss, Deborah; Meholli, Mimoza; Mabie, Peter
Abstract : We report an intriguing case of corticosteroid-resistant bulbar neurosarcoidosis responding to intravenous immunoglobulin. A 37-year-old man presented with dysphagia to solids and liquids, dysphonia, fatigue and 50 lb weight loss over 2 months. We suspected sarcoidosis, based on an elevated serum angiotensin-converting enzyme concentration and hilar lymphadenopathy on chest imaging; we subsequently confirmed this after transbronchial biopsy found non-caseating granulomas. MR scan of brain was normal; barium swallow showed severe oropharyngeal dysphagia and electromyography identified bulbar muscle denervation. He took corticosteroids for 3 weeks without improvement, requiring a percutaneous endoscopic gastrostomy tube for nutrition, but then he promptly improved with a 2-day course of intravenous immunoglobulin. Although there have been a few reports of intravenous immunoglobulin helping peripheral neurosarcoidosis, this case suggests that it also helps bulbar neurosarcoidosis. This case shows that bulbar neurosarcoidosis can mimic the clinical and electrophysiological features of fatal neurological disorders such as progressive bulbar palsy. The case illustrates the diagnostic challenge particularly when imaging is inconclusive and there is no response to corticosteroids. It also suggests that intravenous immunoglobulin can be considered before cytotoxic therapy for corticosteroid-resistant neurosarcoidosis, particularly in decompensated patients, given its favourable side effect profile. We also review the literature on bulbar neurosarcoidosis.